STRATEGI KOMUNIKASI PEMASARAN PENYALURAN KREDIT PEMILIKAN RUMAH ( KPR ) DI MASSA COVID - Vicky Amelia Corinna (MediaKom : Jurnal Ilmiah Komunikasi, 2020)
The purpose of this study is to analyze mortgage marketing strategies during the covid period. This research was conducted at the Asemka branch of BTN, West Jakarta.Case study method used to process data. Data analysis used an in-depth interview process with the main informant, namely Mr. Ginanjar as the head of the Asemka branch office, West Jakarta. The results of the study indicate that product quality and service quality greatly influence customer decision making for mortgages at BTN. Furthermore, satisfaction has a positive effect on customer loyalty. BTN Asemka branch in the city of West Jakarta, suggested using the AIDA communication model in improving communication in marketing.